2019
DOI: 10.1038/s41598-019-43112-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and butyrate level changes associated with the long-term administration of proton pump inhibitors to old rats

Abstract: The association between adverse effects of PPI and gut microbiota in old age has yet to be elucidated. We assessed changes in the gut microbiota and butyrate levels following the long-term administration of PPIs to old rats and investigated their associations. F344 aged male rats were fed a PPI-supplemented diet for 50 weeks. The ileal microbiota was analysed by metagenomic sequencing of the 16S rRNA, while the butyrate concentration was measured by high-performance liquid chromatography. We observed a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…It also helps in the digestion process, and methane production [ 41 ]. However, the specific function of Clostridium saudiense is still needs to be explored in swine gut microbiome [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also helps in the digestion process, and methane production [ 41 ]. However, the specific function of Clostridium saudiense is still needs to be explored in swine gut microbiome [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from the frozen fecal samples using a QIAamp DNA Stool Mini Kit (Qiagen, Valencia, CA, United States) according to the manufacturer’s recommendations. PCR amplification was carried out using the primers targeting the V3 to V4 regions of the 16S rRNA gene of the extracted DNA to conduct metagenome sequencing, and were as follows 59 : 341F (5′-TCGTCGGCAGCGTCAGATGTGTATAAGAGACAGCCTACGGGNGGCWGCAG-3′) and 805R (5′-GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAGGACTACHVGGGTATCTAATCC-3′). Next procedures were performed as described previously 59 .…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification was carried out using the primers targeting the V3 to V4 regions of the 16S rRNA gene of the extracted DNA to conduct metagenome sequencing, and were as follows 59 : 341F (5′-TCGTCGGCAGCGTCAGATGTGTATAAGAGACAGCCTACGGGNGGCWGCAG-3′) and 805R (5′-GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAGGACTACHVGGGTATCTAATCC-3′). Next procedures were performed as described previously 59 . Briefly, the identity of the PCR products was confirmed using electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported that α-diversity was significantly lowered in proton pump inhibitor (PPI) users [51]. Sun Min Lee reported that long-term PPI administration significantly reduced the intestinal flora α-diversity in 2-year-old rats, while no significant α-diversity reduction was seen in 74-week-old rats [52]. In other words, changes in α-diversity due to PPI administration occurred only in older rats.…”
Section: Microbiota α-Diversitymentioning
confidence: 97%